2017
DOI: 10.3399/bjgpopen17x101073
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of integrated early child development care at private clinics in poor urban Pakistan: a mixed methods study

Abstract: BackgroundIn poor urban Pakistan, private GP clinics lack adequate services to promote early child development (ECD) care. A clinic-based contextualised ECD intervention was developed for quarterly tool-assisted counselling of mothers.AimTo explore the experience and implementation of ECD intervention by the private care providers and clients, for further adaptation for scaling of quality ECD care, at primary level private healthcare facilities in Pakistan.Design & settingA mixed methods approach using quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In Pakistan, there has been limited reported experience of using ASQ-3 to measure all five domains of child development. 3032 Similarly, clinic-based measurement of child development has not been tested before. In the present study, the caregiver responses were supplemented by on-site observation by a trained assessor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Pakistan, there has been limited reported experience of using ASQ-3 to measure all five domains of child development. 3032 Similarly, clinic-based measurement of child development has not been tested before. In the present study, the caregiver responses were supplemented by on-site observation by a trained assessor.…”
Section: Discussionmentioning
confidence: 99%
“…The process evaluation has shown that clinic-based delivery of ECD care is feasible for providers, and acceptable for mothers and families living in poor urban localities. 30…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from Pakistan in private outpatient clinics with mothers of young children found that counseling focused on promoting development were more engaging and helpful than the usual/standard care provided by paediatric consultants [15]. However, the programme was funded through a research grant and scale-up of the innovation will likely remain dependent on philanthropy for further implementation.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the ECD and disability research and programmatic work in Pakistan is community-based in the public sector with scarce evidence of collaboration from the private health sector. A study with private outpatient clinics with mothers of young children found that counseling focused on promoting development were more engaging and helpful than the usual/standard care provided by pediatric consultants (20). However, the program was funded through a research grant, and scale-up of the innovation will likely remain dependent on philanthropy for further implementation.…”
mentioning
confidence: 99%